Metodologías activas de enseñanza y su influencia en el desarrollo de la inteligencia emocional en los estudiantes de la UE. Francisco Robles, Babahoyo. 2022 - Albán Cuestas, Julissa Josefina (2023)
Currently, active teaching methodologies are characterized by a cognitive approach and the development of skills, which omits the importance of the student's attitudinal predisposition and the role that emotions play in education, mainly in the construction of meaningful learning. Thus, due to the demotivation, stress and low academic performance caused by the tension caused by the Covid-19 pandemic and the social conflicts that are part of the context of the student; The objective of this paper is to determine the way in which active teaching methodologies influence the development of emotional intelligence in EU students. Francis Robles. Study that is carried out through a descriptive, explanatory type of research, and of a non-experimental design. At the same time, it takes as a study sample 40 students who make up the sixth year of Basic General Education, who through the survey reflect difficulties to assimilate the information and practice what they have learned, just as the classes are not interesting. For their part, the results indicate that students choose to hide their sadness, are unable to control their anger, and their state of mind intervenes in concentration. Hence, statistically it is verified that the relationship between the variables is high (47.5%). For this reason, it is concluded that active teaching methodologies significantly influence the development of emotional intelligence, so its strengthening in education allows a comprehensive training of the student.